Global business strategies in crisis : strategic thinking and development - Hacioğlu, Ümit; Dinçer, Hasan; Alayoğlu, Nihat (Springer, 2017)
As the world is currently in the midst of financial and economic crises, this collection of expert contributions focuses on strategy formation and implementation at various organizational levels to address the challenges ahead. The latest economic turmoil and its ongoing impact on business performance are compelling top managers to develop effective business strategies and redefine the boundaries of their operational and strategic activities. On one hand, tremendous challenges in the competitive business environment have become a source of global threats for many small entrepreneurs. On the other, investors faced with today?s volatile economic conditions demand more gains on their capital investments to counter-balance the growing risk of global threats. This book explores the question as to whether it is possible to efficiently and effectively address these threats and obstacles. Are managers capable of planning and implementing strategic actions? What should the major managerial strategy be in order to overcome fluctuations in a market-oriented society?
Keywords: Strategic planning.; Risk management.; Management science.; elektronické knihy; electronic books